Spoken Word Segmentation in First and Second Language: When ERP and Behavioral Measures Diverge - Gilbert, Annie C.; Lee, Jasmine G.; Coulter, Kristina; Wolpert, Max A.; Kousaie, Shanna; Gracco, Vincent L.; Klein, Denise; Titone, Debra; Phillips, Natalie A.; Baum, Shari R. (Frontiers in Psychology, 2021)
Previous studies of word segmentation in a second language have yielded equivocal results. This is not surprising given the differences in the bilingual experience and proficiency of the participants and the varied experimental designs that have been used. The present study tried to account for a number of relevant variables to determine if bilingual listeners are able to use native-like word segmentation strategies. Here, 61 French-English bilingual adults who varied in L1 (French or English) and language dominance took part in an audiovisual integration task while event-related brain potentials (ERPs) were recorded. Participants listened to sentences built around ambiguous syllable strings (which could be disambiguated based on different word segmentation patterns), during which an illustration was presented on screen. Participants were asked to determine if the illustration was related to the heard utterance or not. Each participant listened to both English and French utterances, providing segmentation patterns that included both their native language (used as reference) and their L2. Interestingly, different patterns of results were observed in the event-related potentials (online) and behavioral (offline) results, suggesting that L2 participants showed signs of being able to adapt their segmentation strategies to the specifics of the L2 (online ERP results), but that the extent of the adaptation varied as a function of listeners’ language experience (offline behavioral results).